Life (dis)satisfaction and decision to migrate: Evidence from central and Eastern Europe - Vladimir Otrachshenko; Olga Popova (Osteuropa-Institut Regensburg, 2011)
This paper provides the first evidence regarding the impact of life satisfaction on the individual intention to migrate. The impact of individual characteristics and country macroeconomic variables on the decision to migrate is analyzed in one framework. Differently from other studies, we allow for life satisfaction to serve as a mediator between macroeconomic variables and the intention to migrate. Using the Eurobarometer survey for 27 Central Eastern (CEE) and Western European (non-CEE) countries, we test the predictions of our theoretical model and find that people dissatisfied with life have higher intention to migrate. We have not enough evidence that the macroeconomic conditions affect the intention to migrate directly, but these factors do affect migration decision indirectly through life satisfaction. We also find that at all levels of life satisfaction, the unemployed, middle-age individuals with low or average income from urban areas at all levels of education have higher intentions to migrate from CEE countries than from non-CEE countries.
Keywords: J61; I31; 330; life satisfaction; migration; decision making; Zufriedenheit; Internationale Wanderung; Entscheidung; Osteuropa